The Airlines e-Ticketing System in Malaysia : A study on Customer Behavior - Ismail, Nor Alina; Sulaiman, Nor Anis Asma; Rashid, Aida Maryani Abdul (International Journal of Psychosocial Rehabilitation, 2020)
The improvement of ICT has forced Airline organisations into hard competition. This technology will help to ease the process of online transactions (e-transaction) between company and customer because in this new era of technology usage, both company and customer are the important elements which the airline organisations are concentrating on, in order to manage customer relationship and customer satisfaction for a long term period. This paper report a study that investigated users’ perception or behavior towards airline e-ticketing system in Malaysia. This paper also attempts to study on why people use this technology while some of them still stick with the manual system which is buying ticket at counter. The finding shows that, factors such as price, internet security, website design play an importants role in order to make customer purchase ticket online. However, further study need to be conduct in order to investigate another factors on customers behavior in making decision to use the internet as a mean of buying online rather than the traditional way.